Discovery of melanin‐concentrating hormone receptor 1 in brown adipose tissue. Issue 1 (27th January 2021) - Philippe, Cécile; Klebermass, Eva‐Maria; Balber, Theresa; Kulterer, Oana C.; Zeilinger, Markus; Egger, Gerda; Dumanic, Monika; Herz, Carsten T.; Kiefer, Florian W.; Scheuba, Christian; Scherer, Thomas; Fürnsinn, Clemens; et al.
Abstract: Although extensive research on brown adipose tissue (BAT) has stimulated optimism in the battle against obesity and diabetes, BAT physiology and organ crosstalk are not fully understood. Besides BAT, melanin‐concentrating hormone (MCH) and its receptor (MCHR1) play an important role in energy homeostasis. Because of the link between hypothalamic MCH neurons and sympathetic BAT activation via β‐adrenoceptors, we investigated the expression and physiological role of the MCHR1 in BAT. MCHR1 was detected in rodent and human BAT with RT‐qPCR and western blot analyses. In vivo imaging in rats used the glucose analog [ 18 F]FDG and the MCHR1‐tracer [ 11 C]SNAP‐7941. We found that the β3‐adrenoceptor (ADRB3) agonist CL316, 243 increased [ 11 C]SNAP‐7941 uptake in BAT. Additionally, a pharmacological concentration of SNAP‐7941—a low‐affinity ADRB3 ligand—stimulated [ 18 F]FDG uptake, reflecting BAT activation. In cultured human adipocytes, CL316, 243 induced MCHR1 expression, further supporting a direct interaction between MCHR1 and ADRB3. These findings characterized MCHR1 expression in rodent and human BAT for the first time, including in vitro and in vivo data demonstrating a link between MCHR1 and the β3‐adrenergic system. The presence of MCHR1 in BAT emphasizes the role of BAT in energy homeostasis and may help uncover treatment approaches for obesity. Abstract : Our findings here describe the expression of melanin‐concentrating hormone receptor 1 (MCHR1) in rodent and human brown adipose tissue (BAT). In vitro and in vivo data demonstrate a link between MCHR1 and the β3‐adrenergic system. The presence of MCHR1 in BAT emphasizes its role in energy homeostasis and may open new possibilities for treatment of obesity.